Probabilistic safety assessment of historical railway masonry arch bridges - Moreira, Vicente Novo (2015)
The paper presents the probabilistic methodologies of safety assessment of existing structures, in particular applicable to bridges and viaducts. Attending to safety assessment requirements, there are different levels of reliability. The core objectives are to analyse the current load bearing capacity and the in-service behaviour with the maximum accuracy and minimal effort and costs. The present methodology consists on determining the load-carrying capacity (Ultimate Limit State) of masonry arch bridges, by using a probabilistic approach and Limit States principles. Geometric, material and load characterizations, as variable’s complexity and inherent uncertainties will also be shown. To determine the load-carrying capacity, a limit analysis approach, based on mechanisms, will be employed. Due to high computational costs that probabilistic safety assessment requires, a previous sensitivity analysis will be performed in order to reduce those costs. The incorporation of new information, from monitoring or characterization tests, by application of Bayesian methodologies, will be described as well. The presented probabilistic approach throughout this paper will be applied to the case study of Durrães Viaduct.